-3.36=b+5.12

Simple and best practice solution for -3.36=b+5.12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3.36=b+5.12 equation:


Simplifying
-3.36 = b + 5.12

Reorder the terms:
-3.36 = 5.12 + b

Solving
-3.36 = 5.12 + b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-1b' to each side of the equation.
-3.36 + -1b = 5.12 + b + -1b

Combine like terms: b + -1b = 0
-3.36 + -1b = 5.12 + 0
-3.36 + -1b = 5.12

Add '3.36' to each side of the equation.
-3.36 + 3.36 + -1b = 5.12 + 3.36

Combine like terms: -3.36 + 3.36 = 0.00
0.00 + -1b = 5.12 + 3.36
-1b = 5.12 + 3.36

Combine like terms: 5.12 + 3.36 = 8.48
-1b = 8.48

Divide each side by '-1'.
b = -8.48

Simplifying
b = -8.48

See similar equations:

| b-5+3b=32 | | -7x-8+9x=4 | | 5x+3=x+4 | | a=2l+2w | | -6x+6=4(2x+1) | | x^2+15x-2=0 | | 4.5=15+15x | | -23=34*t | | (25)-(-5)= | | a=21+2w | | b-8+8b=29 | | 15y=14+2(5y+6) | | 10(6x+11)= | | 6x+6=4(2x+1) | | 4lnx=20 | | -10x-11+12x-15=-4 | | 4-(3x+6)=-10 | | 5(x-8)=-11 | | b/13-9b/13=40/13 | | 12x-4=24x+4 | | (-2)+2(12)=a | | -10x-11+12x-15=4 | | 3y+4-y=10+y | | 3.2g+6=6+3.2g | | -4x-2(3x-7)=-6 | | 22a-2a+43.465=3a | | 3y-1+4y=8-9+7y | | 4=4(1-4x)+8(x-4) | | 3[-4-(-4+5)]= | | 3(y-8)=-y | | 7x(6x-2)=180 | | 4x=3y-7-2x |

Equations solver categories